Invincible summer : a novel - Adams, Alice, 1926-1999 (Little, Brown and Company, 2016)
Four close friends who graduate college together in 1998 venture off to pursue their fortunes in the new millennium, but find themselves drawn back together twenty years later amidst broken dreams, lost jobs, and shattered relationships.